Mutations in the X-Linked Retinitis Pigmentosa Genes RPGR and RP2 Found in 8.5% of Families with a Provisional Diagnosis of Autosomal Dominant Retinitis Pigmentosa - Churchill, Jennifer D. (The Association for Research in Vision and Ophthalmology, 2013)
PURPOSE. We determined the fraction of families in a well-characterized cohort with a provisional diagnosis of autosomal dominant retinitis pigmentosa (adRP) that have disease-causing mutations in the X-linked retinitis pigmentosa GTPase regulator (RPGR) gene or the retinitis pigmentosa 2 (RP2) gene. METHODS. Families with a provisional clinical diagnosis of adRP, and a pedigree consistent with adRP but no male-to-male transmission were selected from a cohort of 258 families, and tested for mutations in the RPGR and RP2 genes with di-deoxy sequencing. To facilitate testing of RPGR in “adRP” families that had no male members available for testing, the repetitive and purine-rich ORF15 of RPGR was subcloned and sequenced in heterozygous female subjects from 16 unrelated families. RESULTS. Direct sequencing of RPGR and RP2 allowed for identification of a disease-causing mutation in 21 families. Of these “adRP” families 19 had RPGR mutations, and two had RP2 mutations. Subcloning and sequencing of ORF15 of RPGR in female subjects identified one additional RPGR mutation. Of the 22 mutations identified, 15 have been reported previously. CONCLUSIONS. These data show that 8.5% (22 in 258) of families thought to have adRP truly have X-linked retinitis pigmentosa (XLRP). These results have substantive implications for calculation of recurrence risk, genetic counseling, and potential treatment options, and illustrate the importance of screening families with a provisional diagnosis of autosomal inheritance and no male-to-male transmission for mutations in X-linked genes. Mutations in RPGR are one of the most common causes of all forms of retinitis pigmentosa.